1992
DOI: 10.1136/ard.51.4.465
|View full text |Cite
|
Sign up to set email alerts
|

Increase in neutrophil Fc gamma receptor I expression following interferon gamma treatment in rheumatoid arthritis.

Abstract: The therapeutic potential of interferon y (IFN y) in a number of disease states is still being explored, but progress is hampered by the lack of a suitable measure of in vivo biological activity. To assess the in vivo biological effects of recombinant human IFN y (rhIFN y), 14 patients were studied in a randomised, prospective, double blind, placebo controlled trial of this cytokine for the treatment of rheumatoid arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 16 publications
2
9
0
Order By: Relevance
“…Whereas FcγR expression is rather well-described qualitatively, there is only quite limited information available on actual numbers of FcγR expressed by the different leukocyte populations (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). To our knowledge there is no publication, where such numbers have been determined for the main leukocyte populations in parallel, even though Antal-Szalmas et al (18) and the group of Guyre (19,(22)(23)(24)(25) provided data on human neutrophils and monocytes. In addition, work on FcγR cell surface numbers often dates back to times, where certain cell subpopulations with an entirely different FcγR repertoire (such as classical and non-classical monocytes), had not been distinguished.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas FcγR expression is rather well-described qualitatively, there is only quite limited information available on actual numbers of FcγR expressed by the different leukocyte populations (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). To our knowledge there is no publication, where such numbers have been determined for the main leukocyte populations in parallel, even though Antal-Szalmas et al (18) and the group of Guyre (19,(22)(23)(24)(25) provided data on human neutrophils and monocytes. In addition, work on FcγR cell surface numbers often dates back to times, where certain cell subpopulations with an entirely different FcγR repertoire (such as classical and non-classical monocytes), had not been distinguished.…”
Section: Introductionmentioning
confidence: 99%
“…The patients are described under subjects, group 4. represents an effect of granulocyte colony-stimulating factor (G-CSF), the concentration of which is markedly elevated in cord blood from most term and preterm neonates [9]. In addition to G-CSF, interferon-g (IFN-g) is the only cytokine known to induce the expression of CD64 on neutrophils [10][11][12][13]. Both these cytokines are produced in response to bacterial infections.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro experiments also showed that expression of FcγRIIIa is up-regulated by TGF-β, IFN-γ and M-CSF [138]; expression of FcγRI is up-regulated by G-CSF and IFN-γ [139–141]. Also, rheumatoid arthritis patients treated with IFN-γ have increase in neutrophil FcγRI expression [142]. Dysregulation and dysfunction of FcγRs are often observed at sites of inflammation in autoimmune diseases.…”
Section: Future Strategiesmentioning
confidence: 99%